(untitled) (Prostor, 2024)
The study aims to evaluate the impact of a public art project within the framework of ecological urban planning on various parameters: the perception of the environment, the image of the area, and the level of neighborhood attachment among residents and visitors. The objective of the public art project was to integrate artistic design into ecological urban planning. The primary research method involved surveying local residents and visitors in the Xiangjiang New District (Changsha, China) in 2020 and 2023. A statistical analysis of the survey results revealed significant changes in the perception of certain properties of the urban environment, such as complexity, naturalness, typicality, openness, and consistency. The results also indicated that the project enhanced the overall image of the city and key aspects such as dynamism, sociability, innovation, creativity, and quality of life. These findings can facilitate the more effective integration of public art into ecological design and deepen the understanding of its impact on positive socio-cultural and environmental aspects in cities, thereby benefiting urban planners, designers, and government authorities.